Bridge Scour - Muñoz, Edgar (2025)
In the present paper an evaluation of scour problems bridges of the Colombian National Highways has been developed; based on the principal inspection and inventory module of the Colombian Bridge Administration System (SIPUCOL), which has been implemented since 1996 by the National Highways Institute (INVIAS). SIPUCOL has been an essential tool to maintain security and functionality of Colombian bridges. This article presents the amount, evolution and classification of damages, based on visual inspections, maintenance, studies performance and rehabilitation works. In this document it has been included all the collapsed bridges which main cause of collapse has been scour. To prevent bridges failure risks, taking into account that scour is a complex problem, some recommendations have been made about the inspection methodology, the study’s quality and the analytic research implementation.